2016 IEEE International Conference on Robotics and Automation (ICRA) 2016
DOI: 10.1109/icra.2016.7487348
|View full text |Cite
|
Sign up to set email alerts
|

Grasp detection for assistive robotic manipulation

Abstract: In this paper, we present a novel grasp detection algorithm targeted towards assistive robotic manipulation systems. We consider the problem of detecting robotic grasps using only the raw point cloud depth data of a scene containing unknown objects, and apply a geometric approach that categorizes objects into geometric shape primitives based on an analysis of local surface properties. Grasps are detected without a priori models, and the approach can generalize to any number of novel objects that fall within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 26 publications
0
36
0
7
Order By: Relevance
“…The authors then matched these parts against template grasps. Similarly, Jain and Argall 20 described an algorithm to match whole real objects against geometric shapes (i.e. spheres, cylinders, boxes) rather than parts of them.…”
Section: Object Reconstruction and Template Grasp Retrievalmentioning
confidence: 99%
“…The authors then matched these parts against template grasps. Similarly, Jain and Argall 20 described an algorithm to match whole real objects against geometric shapes (i.e. spheres, cylinders, boxes) rather than parts of them.…”
Section: Object Reconstruction and Template Grasp Retrievalmentioning
confidence: 99%
“…The authors in [18] propose an approach that takes 3D point-cloud and hand geometric parameters as the input, then search for grasp configurations within a lower dimensional space satisfying defined geometric necessary conditions. Jain et al [19] analyze the surface of every observed point cloud cluster and automatically fit spherical, cylindrical, or box-like shape primitives to them. The method uses a predefined strategy to grasp each shape primitive.…”
Section: Introductionmentioning
confidence: 99%
“…Object grasping problem is usually approached based on physical analysis (classical approach) [1]- [4], geometry [5]- [8], or machine learning (ML) [9]- [11]. The first requires sufficient knowledge about the object (shape, mass, material, ...…”
Section: Introductionmentioning
confidence: 99%
“…Their algorithm computes grasping points in lower than 1 second duration, however is limited to 2 fingered grippers, and no data regarding grasping success rate is presented. Grasp planning of unknown objects from point cloud data is presented in [5], using geometric information to categorize objects into shape primitives, with predefined strategies for each. Success rate of 82% is achieved, however no computation time data was reported.…”
Section: Introductionmentioning
confidence: 99%